Exploring an athletic talent development environment in China: A case study of a sport-friendly high school - Jiang, X.; Guo, J.; Chen, Z. (Psychology of Sport and Exercise, 2024)
This case study utilized the holistic ecological approach (HEA) to explore a successful athletic talent development environment (ATDE) in China. As a case, we selected a basketball team in one Shanghai sport-friendly high school with outstanding individual and team achievements and aimed at (a) describing the ATDE, and (b) identifying environmental success factors (ESF). Using participant observations, document analysis, informal talks, and formal interviews with key stakeholders, including coaches, teachers, athletes, and administrators from sports and education departments, we derived the ATDE and ESF empirical models. The findings showed that (a) the ATDE demonstrated effective interactions between macro- and micro-levels, and (b) the experienced head coach, dedicated assistant coach, and support from athletes` parents contributed to overcoming barriers of preconditions (e.g., limited financial and human resources) within the environment. Further, a coherent and robust cultural paradigm led by the head coach helped the environment maintain its success for a long period. Although some features are similar to successful ATDEs in other countries, unique characteristics (e.g., not prioritizing athletes` autonomy) specific to this ATDE within the Chinese cultural context have been identified. Our findings supplement current studies on ATDEs using the HEA and reflect the environment within Chinese context, offering insights for researchers and practitioners.